'From boom to where?': the impact of crisis on work and employment in Indian BPO. (July 2014) - Taylor, Phil; D'Cruz, Premilla; Noronha, Ernesto; Scholarios, Dora
<x xml:space="preserve">Abstract</x> This article locates Indian business process outsourcing (BPO) within the global supply chains of business services delivery and an international division of service labour. It acknowledges the BPO market's essential dependence on demand from lead firms in the United States and United Kingdom. Drawing on a conceptual synthesis of the Global Commodity Chain, Global Value Chain and Global Production Network frameworks, the article examines the impact of 2008's financial crisis on employment, work organisation and the experience of work in Indian BPO. Employer/industry sources and employee interviews reveal reconfigured local labour market dynamics, tightened work discipline, an extensification of working time, work intensification and unprecedented growth in job insecurity. Such changed characteristics suggest a watershed that raises questions concerning the sustainability of models of BPO work constructed in pre‐crisis years.